The Potent Respiratory System of Osedax mucofloris (Siboglinidae, Annelida) - A Prerequisite for the Origin of Bone-Eating Osedax? - Huusgaard, Randi S. (Public Library of Science, 2012)
Members of the conspicuous bone-eating genus, Osedax, are widely distributed on whale falls in the Pacific and Atlantic Oceans. These gutless annelids contain endosymbiotic heterotrophic bacteria in a branching root system embedded in the bones of vertebrates, whereas a trunk and anterior palps extend into the surrounding water. The unique life style within a bone environment is challenged by the high bacterial activity on, and within, the bone matrix possibly causing O(2) depletion, and build-up of potentially toxic sulphide. We measured the O(2) distribution around embedded Osedax and showed that the bone microenvironment is anoxic. Morphological studies showed that ventilation mechanisms in Osedax are restricted to the anterior palps, which are optimized for high O(2) uptake by possessing a large surface area, large surface to volume ratio, and short diffusion distances. The blood vascular system comprises large vessels in the trunk, which facilitate an ample supply of oxygenated blood from the anterior crown to a highly vascularised root structure. Respirometry studies of O. mucofloris showed a high O(2) consumption that exceeded the average O(2) consumption of a broad line of resting annelids without endosymbionts. We regard this combination of features of the respiratory system of O. mucofloris as an adaptation to their unique nutrition strategy with roots embedded in anoxic bones and elevated O(2) demand due to aerobic heterotrophic endosymbionts.